On the effect of fire on pipelines (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
Emergency damage to a pipeline may lead to the occurrence of a fire. The nature ofthe flame can vary. This paper considers the case of a jet flame. The impact of a jet flame is oftenunderestimated, since there are fairly effective methods for combating this phenomenon, and it isbelieved that it does not require immediate action to prevent unforeseen consequences. However, ifa parallel pipeline or containers with flammable products are located nearby, a domino effect mayoccur, i.e., damage to the pipeline, ignition of transported products, equipment, as well as threats tohuman life and buildings.This work presents results obtained during an experimental study of the impact of an acousticjet flame on a pipe containing stagnant gas or water. Using sensors, the temperature of the flameimpinging on a pipe located at a fixed distance was studied. Temperature changes were examined asa function of heating time, fire intensity, and position on the pipe. After 19.5 s, an initial increase inthe air temperature inside the pipe to about 20 °C was recorded; after 150 s it rose to a maximum of600 °C, and to about 800 °C after approximately 360 s. In the second stage of the experiment, whenthe pipe contained water, the heating rate in the wall region in contact with the liquid wassignificantly lower than in the first stage of the experiment. The maximum temperature reachedonly about 150 °C. Based on the temperatures of the jet flame and the pipe, the heat fluxes reachingthe pipe and the corresponding heat transfer coefficients were determined. The study demonstratedthe necessity of investigating the effects of jet flames to ensure fire protection, in particular byproviding a safe distance between pipelines. The obtained results can be applied to modeling thepossibility of chain (domino) damage effects in pipeline networks.
Keywords: jet fire; flame impact; domino effect; heat flux; pipeline